Sarcoidosis mimicking breast cancer: a staging challenge - Pereira, Antonio Augusto Claudio; Zaia, Rebecca Dias; Oishi, Denise; Vianna, Maria Regina; Pimentel, Flávio; Ades, Felipe (Brazilian Journal of Oncology, 2020)
Sarcoidosis is often an asymptomatic condition. Most patient are unaware of their diagnostic. It has specific pathological characteristics at microscopic evaluation; however, in imaging tests it can mimic other conditions. Breast cancer is the most common cancer among women. Staging breast cancer patients with sarcoidosis can be challenging as the differential diagnosis between sarcoidosis lesions and metastasis can be difficult by radiologic evaluations. Here we describe the conduction of such a case highlighting the importance of the clinical evaluation and the utility of complementary imaging tests and tissue evaluation in this setting.
Keywords: Breast neoplasms; Sarcoidosis; Positron-emission tomography; Neoplasm metastasis